Enantioselective Oxidative Homocoupling of 2-Oxindoles with a Chiral Bisguanidinium Hypoiodite Catalyst - Odagi, Minami; Shimizu, Yuta; Sugimoto, Kota; Mori, Io; Xu, Ban; Tan, Choon Hong; Nagasawa, Kazuo (Synlett, 2024)
The bisoxindole motif is present in a variety of biologically active compounds. Here, we report an enantioselective oxidative homocoupling reaction of 2-oxindoles in the presence of a chiral bisguanidinium hypoiodite catalyst, providing access to the corresponding optically active bisoxindoles in excellent yields and with moderate to high diastereo- and enantioselectivities.
Keywords: guanidinium compounds; hypoiodites; oxidative coupling; enolate coupling; bisoxindoles; asymmetric catalysis